Implementasi Peraturan Bupati tentang Pengelolaan Sampah Rumah Tangga Perspektif Siyasah Tanfidziyah di Kabupaten Lampung Selatan - Sulis Setiawati (Jurnal Hukum Lex Generalis, 2026)
Household waste issues pose a serious challenge for local governments, requiring well-planned and sustainable management. Ineffective waste management not only results in a decline in environmental quality but also has the potential to generate public health problems, environmental pollution, and a reduction in the aesthetics and overall livability of the area. This study aims to analyze the implementation of policies on the reduction and management of household waste as stipulated in Article 2 Paragraph 1 (a) of the Regent Regulation of South Lampung Number 18 of 2024, implemented by the Environmental Agency of South Lampung Regency, and to examine it from the perspective of Siyasah Tanfidziyah. This research employs a qualitative method with a field-based approach through observation, interviews, and documentation. The findings indicate that the implementation of the policy has not been optimal due to limited infrastructure and low levels of public awareness. This condition has resulted in an increasing volume of improperly managed waste and the failure to achieve policy objectives in creating a clean and healthy environment. From the perspective of Siyasah Tanfidziyah, this reflects the suboptimal execution of local government responsibilities in promoting public welfare (maslahah ‘ammah).